Planning for active office intervention in Thailand: survey and in-depth interview of university employees - Raweewan Maphong; Kasem Nakhonket; Suchitra Sukonthasab (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - This study aimed to explore knowledge, attitude, behavior and causes of sedentary behavior (SB) among office workers and guidelines for active office intervention. Design/methodology/approach - The study was comprised of a survey and an interview. In total, 39 nonacademic office workers responded to the Past-day Adults Sedentary Time-University (PAST-U) and workplace sitting break (SITBRQ) questionnaire to measure SB level, sitting bout, frequency and duration of sitting interrupted in 1 h and in whole working hours. Eleven executives and staffs participated in in-depth interviews to understand knowledge, attitude, behavior and cause of SB and guidelines for active office intervention. Findings - Participants commonly spend most of their working time in SB (383.85 ± 93.03 min or 6 h 23 min). The interview indicated that at an individual level, participants lack knowledge and understanding of SB. The most common causes of SB are huge workload, personal characteristics and the weather. At the organizational level, there is no policy, no support from colleagues or organizations, while the physical environment is not conducive to reducing SB. Originality/value - The outcomes of the study are used as basic information and guidelines for establishing an active office intervention in accordance with the culture and context of Thai society. There have been studies in Thailand that examine SB but no studies that have been conducted to study basic information on knowledge, attitudes, behaviors and causes of SB to be used in planning active office intervention to reduce SB.